Clinical Use of Electrocardiogram - Lakshmanadoss, Umashankar (IntechOpen, 2023)
This book provides a comprehensive overview of electrocardiogram (ECG), including both the electrophysiological aspects of ECG and how to identify common diseases like coronary artery diseases based on ECG. This book is divided into two sections: "Practical Applications of ECG in Arrhythmias" and "Clinical Use of ECG". Chapters address such topics as an interpretation of intra-cardiac ECG during electrophysiology study, classic ECG features of narrow and wide QRS complex tachycardias, use of ECG in cattle, and use of unshielded magnetocardiography to detect myocardial damage in patients recovering from COVID-19.